Transcriptome and VcCADs gene family analyses reveal mechanisms of blight resistance in rabbiteye blueberry - Lu, Shan-Shan; Liu, Wei; Yang, Li-Juan; Wu, Cui-Lian; Dai, Zhang-Yang; Zhu, Ming-Liang; Gao, Xuan; He, Feng; Xiao, Jia-Xin; Zhu, Bo (Frontiers in Plant Science, 2025)
IntroductionBlueberry branch blight is a severe plant disease primarily caused by Neofusicoccum parvum.MethodsIn this study, one-year-old branches of two rabbiteye blueberries (Vaccinium virgatum): resistant Tifblue ('TF') and susceptible Climax ('DF') were selected as experimental materials, the physiological parameters of two cultivars pre- and post- N. parvum inoculation. Transcriptomic analysis and comprehensive gene family characterization were conducted to examine the differential gene expression.ResultsThe results indicated that 'TF' exhibited higher lignin content and activity levels of peroxidase enzymes (POD), phenylalanine ammonia-lyase (PAL), and cinnamyl alcohol dehydrogenase (CAD) compared to 'DF'. RNA-sequence analysis revealed that at 24 hours post-inoculation, there were 136 and 121 differentially expressed genes related to lignin synthesis in 'TF' and 'DF', respectively. The analysis of these DEGs revealed that numerous of key enzyme genes in lignin synthesis pathways, including PAL, 4CL, CCR, CAD, HCT, COMT and POD were annotated. Additionally, we characterized the CAD gene family, identifying 93 CAD coding genes at the blueberry genome level, which were classified into four subgroups. Most CAD gene promoters contained response elements associated with plant stress resistance pathways. QRT- PCR experiments demonstrated that the expression levels of VcCAD8 and VcCAD62 genes were significantly upregulated at 24 hours post-inoculation.DiscussionThese findings suggest that VcCADs enhance lignin synthesis, improve the resistance of blueberries to shoot blight, and provide novel insights into the defense mechanisms of blueberries against N. parvum.